O39 Improving the evidence-base to understand sti risk reduction capacity: the feasibility and acceptability of linking online behavioural survey data to genitourinary medicine clinic records. (8th June 2017) - Blomquist, Paula; Wayal, Sonali; Mercer, Catherine; Weatherburn, Peter; Reid, David; Hughes, Gwenda
Abstract : Introduction: Behavioural surveys provide insight into the context associated with STI risk, but interpretation is hampered by using self-reported STI history. We aimed to determine the feasibility and acceptability of linking patients' online survey data on STI risk factors with the national surveillance dataset on STI diagnoses (GUMCADv2). Methods: Between May-September 2016, attendees at 16 GUM clinics across England were invited to complete an online survey on knowledge, attitudes, and behaviours around STI risk, using a clinic tablet or personal device. Clinic staff recorded respondents' patient IDs, which we used to link surveys to GUMCADv2 (as well as age, gender, and clinic attendance date). We examined recruitment and linkage success and used Z-test for proportions to assess selection bias. Results: 6283 attendees agreed to participate, and 73.6% (4626) did so, with survey completion higher in those who completed the survey in clinic vs. those who did so at home (87.3% vs 16.8%). 95.9% (4437) of survey respondents were eligible, which was 59.2% of our recruitment target. 91.2% (4046/4437) of participants consented to data linkage, and of these 88.9% (3596) were linked to GUMCADv2. Consent did not differ by age or gender but was higher among MSM than heterosexual men (95.5% vs. 88.4%; p<0.01), and lower among black Caribbean than white participants (87.1% vs 93.8%; p<0.01). Discussion: Online behavioural surveys distributed in GUM clinics with linkage to GUMCADv2 are both highly acceptable to attendees and technically feasible. Staff should encourage survey completion on clinic tablets to maximise recruitment and linkage success.